2019
DOI: 10.1017/s1047951119002786
|View full text |Cite
|
Sign up to set email alerts
|

Association between preoperative respiratory support and outcomes in paediatric cardiac surgery

Abstract: Background:Preoperative mechanical ventilation is associated with morbidity and mortality following CHD surgery, but prior studies lack a comprehensive analysis of how preoperative respiratory support mode and timing affects outcomes.Methods:We retrospectively collected data on children <18 years of age undergoing cardiac surgery at an academic tertiary care medical centre. Using multivariable regression, we examined the association between modes of preoperative respiratory support (nasal cannula, high-flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
1
Order By: Relevance
“…Other studies, however, have failed to demonstrate the association of preoperative MV and extubation failure in broader populations (10, 18, 23, 24). Previous studies have demonstrated the association of preoperative NIV or MV with longer postoperative length of stay (25) and mortality (25–27). None of these studies evaluated for an association with extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have failed to demonstrate the association of preoperative MV and extubation failure in broader populations (10, 18, 23, 24). Previous studies have demonstrated the association of preoperative NIV or MV with longer postoperative length of stay (25) and mortality (25–27). None of these studies evaluated for an association with extubation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative mechanical ventilation is a known predictor of adverse outcomes following paediatric cardiac surgery. 17 In an analysis of 25,476 paediatric congenital heart surgeries, Jacobs et al found that discharge mortality was significantly higher in patients who were mechanically ventilated preoperatively compared to overall mortality for neonates (15.1% versus 9.88%), infants (11.5% versus 2.91%) and children (14.4% versus 0.92%; P <0.001). 18 Similar observations have been described post-mBT shunt surgery.…”
Section: Discussionmentioning
confidence: 99%
“…З усіх цих причин рекомендується раннє відлучення від апарату ШВЛ. Більшість маленьких пацієнтів можна відлучити вже через 6-24 години після кардіохірургічної операції, але деякі пацієнти потребують тривалої ШВЛ (понад 24 години) через ускладнення з боку дихальної системи, зниження серцевої функції або інфекції тощо [6].…”
unclassified